An Improved Energy Saving Technique for Wireless Power Transfer in Near Field Communication Systems - John A Adebisi; Khadeejah A Abdulsalam; Kingsley C. Ijike (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
In this work, an improved communication algorithm was developed to reduce energy wastage in a Near Field Communication (NFC) system using dynamic field Strength scaling technique. With a variable resistor in the reader coil, the field strength of the system was scaled in real-time by adjusting the value of the resistor in relation to distance. This system was tested with the advanced design system's Application Extension Language (AEL) and simulated on Advanced Digital Technology. The results showed a responsive change in the magnetic field when the two scenarios (with and without optimization) were simulated. There was a 66% change in energy transfer within the time frame referenced. Results further indicated that the adoption of the proposed algorithm could help engineers to design a more effective NFC system.